2015
DOI: 10.3402/fnr.v59.27719
|View full text |Cite
|
Sign up to set email alerts
|

Effects of black adzuki bean (Vigna angularis, Geomguseul) extract on body composition and hypothalamic neuropeptide expression in rats fed a high-fat diet

Abstract: BackgroundObesity is often considered to result from either excessive food intake or insufficient physical activity. Adzuki beans have been evaluated as potential remedies for various health conditions, and recent studies have reported their effects on the regulation of lipid metabolism, but it remains to be determined whether they may be effective in overcoming obesity by regulating appetite and satiety.ObjectiveThis study investigated the effect of black adzuki bean (BAB) extract on body composition and hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The overall body mass and the epidermal fat mass were remarkably lowered. In comparison with the high-fat diet fed animals, the serum lipid pro les of the animals supplemented with the BAB (black adzuki bean) containing diet was enhanced [31]. In a study, when experimental rats fedona high-cholesterol diet were supplemented with encased symbiotic microbes, it exponentially lowered the LDL-cholesterol compared to every one of the other groups, and also highly increased the HDL-cholesterol levels [32].…”
Section: Discussionmentioning
confidence: 99%
“…The overall body mass and the epidermal fat mass were remarkably lowered. In comparison with the high-fat diet fed animals, the serum lipid pro les of the animals supplemented with the BAB (black adzuki bean) containing diet was enhanced [31]. In a study, when experimental rats fedona high-cholesterol diet were supplemented with encased symbiotic microbes, it exponentially lowered the LDL-cholesterol compared to every one of the other groups, and also highly increased the HDL-cholesterol levels [32].…”
Section: Discussionmentioning
confidence: 99%
“…These effects were related to the down‐regulation of lipogenic and lipolysis‐related transcriptional factors and the up‐regulation of fatty acid oxidation‐related transcriptional factors (Kim et al., 2017; Lee et al., 2019). Furthermore, reduced food intake was observed in different murine models, which might be attributed to the regulation of the hypothalamic neuropeptide expression (Kim et al., 2015). Specifically, the increased leptin sensitivity induced by the increased expression of leptin receptor (ObRb) down‐regulated the orexigenic neuropeptides and up‐regulated the anorexigenic neuropeptides, resulting in the induction of satiety and suppression of appetite (Kim et al., 2015).…”
Section: Health Benefits Of Adzuki Bean and Its Componentsmentioning
confidence: 99%
“…Furthermore, reduced food intake was observed in different murine models, which might be attributed to the regulation of the hypothalamic neuropeptide expression (Kim et al., 2015). Specifically, the increased leptin sensitivity induced by the increased expression of leptin receptor (ObRb) down‐regulated the orexigenic neuropeptides and up‐regulated the anorexigenic neuropeptides, resulting in the induction of satiety and suppression of appetite (Kim et al., 2015). It was found that the administration of adzuki bean pastes and extracts could decrease the ratio of Firmicutes to Bacteroidetes (Han, Ohashi, et al., 2020; Lee et al., 2019).…”
Section: Health Benefits Of Adzuki Bean and Its Componentsmentioning
confidence: 99%
“…Polyphenols regulate NAFLD by impacting the bile acid metabolism via “cross-talk” among the liver, the brain, and the gut. , BAs cross the BBB and bind to FXR/TGR5 receptors in the brain and inhibit hypothalamic inflammation, thereby weakening NAFLD. Furthermore, BAs can directly bind to FXR/TGR5 receptors in the gut and correspondingly lead to the release of FGF15/GLP-1, which affects the appetite through the hypothalamic signaling pathway, thereby leading to the reduction of FFAs and TG in the liver.…”
Section: Regulation Of Gut Microbiota-derived Metabolitesmentioning
confidence: 99%
“…Figure 6. Polyphenols regulate NAFLD by impacting the bile acid metabolism via "cross-talk" among the liver, the brain, and the gut 60,122. BAs cross the BBB and bind to FXR/TGR5 receptors in the brain and inhibit hypothalamic inflammation, thereby weakening NAFLD.…”
mentioning
confidence: 99%